2005
DOI: 10.3168/jds.s0022-0302(05)73117-9
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Conception Rates Following Detection of Estrus and Timed AI in Dairy Cows Synchronized Using GnRH and PGF2

Abstract: The objective of this study was to compare conception rates of cows exhibiting spontaneous estrus and receiving artificial insemination (AI) before completion of a timed AI protocol with cows that did not display estrus spontaneously, but were inseminated after 1 of 3 GnRH-PGF2alpha protocols. Cows (n = 432) in 2 herds were administered GnRH on d -7 and were tail-chalked daily. Cows detected in estrus before d 0 were inseminated immediately. Cows not detected in estrus by d 0 were administered PGF2alpha and we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
1
3
1
Order By: Relevance
“…venson et al, 2014). These results are in contrast to others that found no difference at first postpartum AI (Gümen et al, 2003;Dalton et al, 2005; or subsequent AI (Giordano et al, 2015;Dolecheck et al, 2016). The experimental design of our study and other similarly designed studies make it difficult to conclude the major cause for this difference (or lack thereof) in fertility between the 2 categories of inseminations, considering cows detected in estrus were bred approximately 10 d earlier than cows bred in the TAI treatment.…”
Section: Discussioncontrasting
confidence: 99%
“…venson et al, 2014). These results are in contrast to others that found no difference at first postpartum AI (Gümen et al, 2003;Dalton et al, 2005; or subsequent AI (Giordano et al, 2015;Dolecheck et al, 2016). The experimental design of our study and other similarly designed studies make it difficult to conclude the major cause for this difference (or lack thereof) in fertility between the 2 categories of inseminations, considering cows detected in estrus were bred approximately 10 d earlier than cows bred in the TAI treatment.…”
Section: Discussioncontrasting
confidence: 99%
“…Our finding that cow parity does not affect FSC is consistent with those of some studies [4,19], but others have shown that FSC rate is affected by cow parity because it was lower in cows with parity ≥4 or 5 than in primiparous cows [7,10]. IDE or timed AI did not affect FSC rate in the present study, which is consistent with some previous studies [27,28]. However, other studies have shown that the FSC rate in cows undergoing AI during a detected estrus is higher than in cows undergoing timed AI following an Ovsynch protocol [17,29].…”
Section: Discussionsupporting
confidence: 93%
“…Yet, when distinct oestrous behaviour is not detected in Ovsynch based synchronization methods combined with timed artificial insemination (timed AI) protocol (Bartolome et al. 2005; Dalton et al. 2005), AI is not always performed by the AI operator.…”
Section: Introductionmentioning
confidence: 99%
“…The synchronization of oestrus or ovulation has been applied frequently to improve fertility and to achieve labour-saving at cattle farms (Pursley et al 1997;LeBlanc 2001;Gabor et al 2002). Yet, when distinct oestrous behaviour is not detected in Ovsynch based synchronization methods combined with timed artificial insemination (timed AI) protocol (Bartolome et al 2005;Dalton et al 2005), AI is not always performed by the AI operator.…”
Section: Introductionmentioning
confidence: 99%